Low-temperature wax pre-filling material for complex-structure multilayer-wall ceramic core and wax pre-filling method

Through the innovative formula and process of low-temperature pre-filling wax materials, the problems of fracture and dimensional accuracy of multi-layer wall ceramic cores in the production process are solved, and a high-strength, low-shrinkage pre-filling wax effect is achieved, which improves production efficiency and product quality.

CN120718463AActive Publication Date: 2025-09-30AVIC BEIJING INST OF AERONAUTICAL MATERIALS
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202511178712.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-22
Publication Date
2025-09-30
Estimated Expiration
2045-08-22

AI Technical Summary

Technical Problem

The existing pre-filled wax material is not strong enough to effectively support the multi-wall ceramic core, which makes the core easy to break and the dimensional accuracy difficult to ensure during the production process. In addition, the shrinkage stress of traditional wax material is too large, affecting the quality of the blade.

Method used

Low-temperature pre-filled wax material is used, which includes paraffin, surfactants, modifiers, fiber components, whisker components, graphene and biomass components. Through specific process flow and parameter control, it is ensured that the material has moderate fluidity, high strength and small solidification shrinkage during the wax injection process, and can effectively support the ceramic core.

Benefits of technology

It significantly improves the fracture resistance of the ceramic core, reduces the fracture rate during the circulation and wax pressing process, ensures the dimensional accuracy and product quality of the blades, reduces residual ash, and improves production efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120718463A_ABST
    Figure CN120718463A_ABST
Patent Text Reader

Abstract

The invention discloses a low-temperature wax pre-filling material for a complex-structure multilayer-wall ceramic core and a wax pre-filling method. The low-temperature wax pre-filling material comprises the following substances in percentage by weight: 46-56% of a paraffin component, 6-9% of a surfactant, 6-9% of a modifier, 6-10% of a fiber component, 5-8% of a whisker component, 1-5% of graphene, 0.5-1% of a biomass component and 12-22% of bonding wax. The wax pre-filling method comprises the following steps: preparing a low-temperature wax pre-filling material; and a wax injection gun is adopted for conducting wax injection and filling on the small-size area in the ceramic core, redundant wax flow is removed after standing, and then the wax pre-filling technology of the ceramic core is completed. The wax pre-filling material is small in solidification shrinkage, moderate in fluidity and high in strength, can be prevented from being broken in the circulation and wax injection process, can be completely removed after a wax injection mold and a shell are manufactured, and is free of ash residues.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of special functional materials for investment casting, and particularly relates to a low-temperature pre-filling wax material and a pre-filling wax method for a ceramic core with a complex structure and a multi-layer wall. Background Art

[0002] In high-end equipment manufacturing, such as aerospace and gas turbines, complex multi-layer ceramic cores are a key process element in achieving precision casting of key components such as high-performance blades. These cores are typically designed with double or even multi-layer walls to accommodate the complex cooling channels within the blades, enhancing heat dissipation and reliability in high-temperature environments. However, multi-layer ceramic cores still face numerous challenges in actual production applications.

[0003] First, the structure of multi-layer ceramic cores is extremely complex, with thin walls (usually 0.5-2mm) and low overall strength (bending strength 10-20MPa). During production circulation (such as handling, storage, transfer, etc.) and wax pressing, even slight collisions, vibrations, or clamping operations can cause the core to crack or even break. According to industry statistics, the fracture rate of double-walled ceramic cores that have not been pre-reinforced during circulation is as high as 30-50%, seriously affecting production efficiency and manufacturing costs. However, the pre-filled wax material in existing technologies is insufficient in strength (compressive strength at room temperature is less than 5MPa), and it is impossible to effectively pre-fill wax and reinforce weak locations of the core (such as double-layer gaps, channel corners, etc.), resulting in a high scrap rate for the core.

[0004] Second, multi-layer ceramic cores contain numerous hollow structures and areas. These areas lack sufficient support during the subsequent wax injection molding process, making them vulnerable points. During the injection molding process, liquid wax must be injected into the mold cavity under a certain pressure. However, due to the lack of internal support in the core, the traditional injection pressure (typically 0.8-2 MPa) can easily cause the hollow areas and hollow structures to deform, collapse, or even collapse, leading to the entire core breaking and becoming scrapped. According to industry statistics, the scrap rate of ceramic cores in aircraft engine blade production due to wax injection pressure accounts for over 40% of all scrapped cores.

[0005] Third, the impact holes (usually 1-3mm in diameter) and transverse ribs (usually 2-5mm in width) on the multi-layer wall ceramic core have small structural dimensions. If pre-wax filling is not performed, these parts will produce uneven shrinkage stress during the wax mold forming stage after wax pressing due to significant differences in wax filling thickness (the thickness difference can be up to 3-10 times), which can easily cause excessive shrinkage and exceed the dimensional accuracy requirements of the blade (usually ±0.05mm), resulting in surface size deviations. In severe cases, the blade will fail to meet the assembly and performance requirements. The probability of such problems occurring in the production of complex surface blades exceeds 25%.

[0006] Currently, the pre-filled wax materials used in the existing technology are mostly single-component paraffin or beeswax. This type of wax shrinks significantly, with the linear shrinkage of paraffin reaching 1.5-3%, and the linear shrinkage of beeswax also between 1-2%. When the wax material is pre-filled into the ceramic core, the shrinkage stress generated during the solidification process far exceeds the bearing limit of the ceramic core, thereby causing the core to crack or fracture. In addition, the fluidity of a single wax material is unstable and difficult to control. It can either be too thin, resulting in wax dripping during the injection process and contaminating the core surface, or it can be too viscous, causing the wax injection gun to clog and making it impossible to successfully fill small structures such as gaps and holes. At the same time, these traditional wax materials have low strength (compressive strength is less than 5MPa at room temperature), and cannot provide effective structural support for the core, making it difficult to prevent the core from breaking during the circulation and wax pressing process.

[0007] In addition, the existing technology's pre-wax filling operation lacks targeted process parameters. For example, the wax injection temperature, pressure, speed and other process parameters are unreasonable, resulting in poor filling effects on complex and small locations such as double-layer gaps, channel gaps, and impact holes. Either the filling is incomplete and forms voids, or the filling is excessive, resulting in waste of wax and difficulty in cleaning, affecting subsequent processes.

[0008] To sum up, the existing pre-filling wax materials and wax filling processes are difficult to meet the production requirements of complex structure multi-layer wall ceramic cores. Therefore, the development of new pre-filling wax materials with low shrinkage, suitable fluidity, high strength and easy removal, and the corresponding pre-filling wax methods, has become the key to solving the current industry technical bottlenecks and promoting the development of precision casting technology. Summary of the Invention

[0009] In order to solve the problems existing in the prior art, the present invention provides a low-temperature pre-filling wax material for a complex structure multi-layer wall ceramic core. The mass percentage of each substance in the low-temperature pre-filling wax material is 46-56wt% of paraffin component, 6-9wt% of surfactant, 6-9wt% of modifier, 6-10wt% of fiber component, 5-8wt% of whisker component, 1-5wt% of graphene, 0.5-1wt% of biomass component, and 12-22wt% of bonding wax, and the sum of the contents of each substance is 100wt%.

[0010] Preferably, the mass percentage of each substance in the paraffin component is 10-15wt% of 46# semi-refined paraffin, 15-21wt% of 48# fully refined paraffin, 19-25wt% of 52# fully refined paraffin, 19-25wt% of 58# fully refined paraffin, and 22-27wt% of 60# fully refined paraffin.

[0011] In any of the above schemes, it is preferred that the mass percentages of the various substances in the surfactant are 40-53 wt % of stearic acid, 25-39 wt % of fatty acid, and 13-27 wt % of sodium dodecylbenzenesulfonate.

[0012] In any of the above schemes, preferably, the mass percentage of each substance in the modifier is 66-80wt% of beeswax and 20-34wt% of polyethylene wax.

[0013] In any of the above schemes, it is preferred that the mass percentage of each substance in the fiber component is 30-43wt% of chopped carbon fiber, 28-40wt% of chopped nylon fiber, and 25-37wt% of chopped aramid fiber; the diameters of the chopped carbon fiber, the chopped nylon fiber, and the chopped aramid fiber are all controlled within the range of 5-15μm, and the aspect ratio is all controlled within the range of 15-25:1.

[0014] In any of the above schemes, it is preferred that the mass percentage of each substance in the whisker component is 25-30wt% for polyamide whiskers, 35-40wt% for chitin whiskers, and 35-40wt% for cellulose whiskers; the diameters of the polyamide whiskers, the chitin whiskers, and the cellulose whiskers are all controlled within the range of 0.5-1μm, and the aspect ratios are all controlled within the range of 5-15:1.

[0015] In any of the above schemes, preferably, the mass percentage of each substance in the biomass component is 35-50wt% of soybean oil, 25-38wt% of chlorella powder, and 22-35wt% of spirulina powder; the chlorella powder and the spirulina powder both include three particle sizes, namely, 18-30μm, 5-18μm, and 0-5μm, and the mass ratios of the particle sizes of 18-30μm, 5-18μm, and 0-5μm are all 1:1.5-2:2.5-3.

[0016] The present invention further provides a method for pre-waxing a complex structure multi-layer wall ceramic core, using any of the above-mentioned low-temperature pre-waxing materials for a complex structure multi-layer wall ceramic core. The pre-waxing method comprises the following steps in order: Step 1: Prepare low-temperature pre-filled wax material according to the designed process flow and process parameters; Step 2: Load the prepared low-temperature pre-filled wax material into the wax injection gun, and control the temperature of the low-temperature pre-filled wax material in the wax injection gun to maintain appropriate fluidity to ensure smooth subsequent wax injection operations; Step 3: According to the designed process parameters, use a wax injection gun to inject wax into the small areas of the complex structure multi-wall ceramic core. After wax injection, let it stand for a certain period of time. After the escaped wax flow is initially solidified, use a tool to clean up the escaped excess wax flow. This completes the pre-wax filling process of the complex structure multi-wall ceramic core, and at the same time, a pre-wax filled complex structure multi-wall ceramic core is obtained.

[0017] Preferably, in step 1, the method for preparing the low-temperature pre-filled wax material comprises the following steps in order: Step 1.1: Weigh all raw materials according to the designed material ratio; Step 1.2: Place all of the chopped carbon fibers, chopped nylon fibers, and chopped aramid fibers in the fiber component and the polyamide whiskers, chitin whiskers, and cellulose whiskers in the whisker component into a V-type mixer, mix them at room temperature for 20-30 minutes at a mixing speed of 100-200 r / min to uniformly disperse the materials, and obtain a fiber-whisker multi-size reinforcement material, which is then removed for later use. Step 1.3: Place all the chlorella powder and spirulina powder of various particle sizes into a V-type mixer and mix them at room temperature for 10-20 minutes at a mixing speed of 100-200 r / min to uniformly mix the materials to obtain composite algae powder, which is then removed for later use. Step 1.4: Place all the surfactant substances, including stearic acid, fatty acid, and sodium dodecylbenzenesulfonate, into a blender and heat while stirring at a speed of 300-400 r / min. After the temperature reaches 90-110°C, continue stirring for 30-40 minutes to allow the substances to blend together to obtain the surfactant. Remove the mixture and keep it warm for later use. Step 1.5: Place all the paraffin components, including 46# semi-refined paraffin, 48# fully refined paraffin, 52# fully refined paraffin, 58# fully refined paraffin, and 60# fully refined paraffin, into a blender and heat while stirring at a speed of 200-300 r / min. After the temperature reaches 80-95°C, continue stirring for 20-30 minutes to completely melt the components. Step 1.6: Maintaining the stirring temperature and stirring speed unchanged, add 80-90 wt% of the surfactant into the blender and continue stirring for 1-2 hours to allow the substances to blend together; Step 1.7: Keeping the stirring temperature and speed constant, add the bonding wax into the blender and continue stirring for 20-30 minutes to allow the substances to blend together. Step 1.8: Keeping the stirring temperature and speed constant, add all the beeswax and polyethylene wax in the modifier into the blender and continue stirring for 1-2 hours to allow the substances to blend together. Step 1.9: Maintaining the stirring temperature and speed, add 10-20 wt% of the surfactant and the soybean oil from the biomass component to the blender and continue stirring for 1-2 hours to allow the substances to blend. Step 1.10: Maintaining the stirring temperature and speed, add the fiber-whisker multi-size reinforcement material and the composite algae powder into the blender and continue stirring for 3-5 hours to ensure that all materials are evenly mixed. Step 1.11: Maintaining the stirring temperature and stirring speed unchanged, add the graphene to the blender and continue stirring for 5-8 hours to ensure that all substances are evenly mixed, thereby obtaining the low-temperature pre-filled wax material; Step 1.12: The prepared low-temperature pre-filled wax material is injection molded, cooled and demolded to obtain an ingot, which is sealed and stored for subsequent pre-filled wax process of complex structure multi-layer wall ceramic core.

[0018] In any of the above solutions, preferably, in step 2, the temperature of the low-temperature pre-filled wax material in the wax injection gun is controlled to be 60-75°C.

[0019] In any of the above schemes, it is preferred that in step three, the small-sized areas in the complex structure multi-layer wall ceramic core include double-layer gaps, channel gaps, transverse ribs, cover plates and impact holes; the wax injection pressure is 0.2-0.5MPa, the wax injection speed is 5-15ml / s, and the straight-line distance between the gun tip of the wax injection gun and the filling position is 5-15mm.

[0020] When injecting wax into double-layer gaps and channel gaps, move the wax injection gun uniformly along the length of the gap at a speed of 10-30mm / s. When injecting wax into transverse ribs and cover plates, select several injection points and inject 0.5-2ml of wax per injection. Repeat the injection process several times. When injecting wax into impact holes, align the wax injection gun tip with the center of the impact hole and inject wax perpendicular to the hole end face until the wax protrudes from the hole end face. After injection, let the wax stand for 1-3 minutes, then use a tool to clean up any excess wax.

[0021] The V-shaped mixer, stirrer (heating type), and wax injection gun used in this invention are all conventional equipment, with no specific requirements for equipment structure or model. Both the chlorella powder and spirulina powder used have three particle sizes: 18-30 μm, 5-18 μm, and 0-5 μm, i.e., 18 μm ≤ ≤ 30 μm, 5 μm ≤ < 18 μm, and 0 μm < < 5 μm. For each particle size range, the material is passed through the upper and lower sieves to obtain a particle size between the upper and lower sieves. For example, for a particle size of 5-18 μm, the material is passed through an 18 μm sieve and a 5 μm sieve to obtain a particle size between 5 and 18 μm. Cellulose whiskers can be purchased with a diameter and aspect ratio that meet the requirements of this invention; there are no specific requirements for their type, model, or preparation.

[0022] The present invention innovatively introduces trace biomass materials, including soybean oil, chlorella powder and spirulina powder. Soybean oil and wax matrix can be well soluble in each other, which not only improves filling fluidity, but also improves wettability. In particular, soybean oil can improve the interfacial wettability between the pre-filled wax material and the inner wall of the ceramic core mold, avoiding the molten wax from forming shrinkage holes or bubbles on the mold surface due to repulsion, thereby ensuring a close fit between the wax layer and the mold after filling, making subsequent molding more complete. Adding chlorella powder and spirulina powder can not only enhance molding stability, but also achieve efficient dewaxing. In particular, chlorella powder and spirulina powder can form microchannels in the wax matrix. After the algae powder is dispersed, tiny pores or channels are constructed in the wax layer. When heated, the molten wax can quickly volatilize through these pores or channels. At the same time, the gas generated by the decomposition of the algae powder itself will also push the residual wax to be discharged, thereby achieving efficient dewaxing.

[0023] For soybean oil, when adding it to the blender, a small amount of surfactant needs to be added at the same time to better blend the soybean oil and paraffin, providing a stable dispersion system for the subsequent addition of fiber components, whisker components, algae powder and graphene.

[0024] For chlorella powder and spirulina powder, you can directly purchase algae powder with three particle sizes that meet the requirements of the present invention, namely, particle size 18-30 μm, particle size 5-18 μm, and particle size 0-5 μm. It is necessary to ensure that the algae powder is dry, without moisture or with a very low moisture content (no more than 1%).

[0025] More preferably, algae powder with a particle size of 50-80 μm is purchased, and the coarse-particle algae powder is pretreated to obtain algae powder with three particle sizes that meet the requirements of the present invention. The present invention pretreats the coarse-particle algae powder according to the following method.

[0026] First, place the coarse-grained chlorella and spirulina powders in a drying oven for drying at 100-120°C for 1-2 hours. After drying, remove the powders and allow them to cool naturally to room temperature. The drying time can be adjusted based on the weight of the powder placed in the drying oven; a drying time of 1-2 hours corresponds to a powder weight of 80-100g.

[0027] The dried chlorella and spirulina powders were then placed in a muffle furnace for a gradient calcination process: heating from room temperature to 200-300°C (200°C ≤ < 300°C) at a rate of 5-10°C / min, holding for 20-30 minutes to slowly remove residual trace moisture and volatile small organic molecules; then heating to 300-500°C (300°C ≤ < 500°C) at a rate of 3-5°C / min, holding for 50-60 minutes to slowly remove organic matter, such as proteins and polysaccharides; and finally heating to 500-650°C (500°C ≤ < 650°C) at a rate of 5-10°C / min, holding for 20-30 minutes, and then cooling to room temperature in the furnace to completely remove residual organic matter. Because the organic matter in the algae powder has poor solubility in the wax matrix and easily aggregates, affecting filling fluidity, calcination is used to completely remove the organic matter.

[0028] Finally, the calcined chlorella powder and spirulina powder are ground and sieved respectively to meet the particle size grade of the present invention.

[0029] The low-temperature pre-wax material and pre-wax method for a complex structure multi-layer wall ceramic core of the present invention have the following beneficial effects: (1) The pre-filled wax material of the present invention has a small solidification shrinkage, and the linear shrinkage rate can be controlled below 0.5%. This is due to the reasonable ratio of multiple wax materials and the synergistic effect of various additives, so that the wax material pre-filled into the multi-layer wall core will not generate excessive stress on the core during the solidification process, thereby avoiding core breakage.

[0030] (2) The pre-filled wax material of the present invention has moderate fluidity and a viscosity that can be controlled within the range of 500-1500 mPa·s (at 60°C). By blending wax materials with different melting points and properties and related components, it can be injected using a wax injection gun. There will be no wax dripping due to the wax liquid being too thin, nor will there be wax blockage due to the wax liquid being too thick, thus ensuring the smooth progress of the filling process.

[0031] (3) The pre-filled wax material of the present invention has high strength, and its compressive strength can reach more than 8MPa at room temperature. The added reinforcing materials such as fiber components and whisker components are combined with the wax matrix, which can effectively strengthen the ceramic core while preventing the wax mold from shrinking too much, and significantly improve the ceramic core's resistance to fracture during the flow or wax pressing process. According to actual tests, the ceramic core treated with the pre-filled wax material of the present invention can reduce its flow fracture rate to less than 5%, and its fracture rate during the wax pressing process can be controlled within 10%. (4) After the wax mold is pressed and the shell is made, the pre-filled wax material of the present invention can be completely removed as the shell is dewaxed (120-160℃) and roasted (800-1200℃), and the residual ash content is less than 0.01%, which reduces the inclusion defect rate of the blade to less than 0.5%, ensuring product quality. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 A photograph of a low-temperature pre-wax material prepared according to a preferred embodiment of the low-temperature pre-wax material and pre-wax method for a complex-structure multi-layered ceramic core of the present invention; Figure 2 for Figure 1 Photographs of ingots obtained by injection molding low-temperature prefilled wax material in the illustrated embodiment; Figure 3 for Figure 1 The embodiment shown is a photo of pre-filled wax for a double-layer gap; Figure 4 for Figure 1 The embodiment shown is a photo of pre-filled wax for a channel gap; Figure 5 for Figure 1 A partial photo of the surface of the ceramic core after wax injection but without wax removal in the embodiment shown; Figure 6 for Figure 1 A partial photo of the surface of the ceramic core after wax injection and wax removal in the embodiment shown; Figure 7 for Figure 1 X-ray inspection photograph of the wax mold after pre-filling with wax in the embodiment shown. DETAILED DESCRIPTION

[0033] In order to further understand the content of the present invention, the present invention will be described in detail below with reference to specific embodiments.

[0034] Example 1: According to a preferred embodiment of the low-temperature pre-filling wax material for complex structure multi-layer wall ceramic cores of the present invention, the mass percentage of each substance in the low-temperature pre-filling wax material is 50wt% of paraffin component, 8wt% of surfactant, 7wt% of modifier, 8wt% of fiber component, 6.2wt% of whisker component, 3wt% of graphene, 0.8wt% of biomass component, and 17wt% of bonding wax.

[0035] The mass percentage of each substance in the paraffin component is 13wt% of 46# semi-refined paraffin, 18wt% of 48# fully refined paraffin, 22wt% of 52# fully refined paraffin, 22wt% of 58# fully refined paraffin, and 25wt% of 60# fully refined paraffin.

[0036] The mass percentages of the surfactants are 48 wt % of stearic acid, 32 wt % of fatty acids, and 20 wt % of sodium dodecylbenzenesulfonate. The mass percentages of the modifiers are 73 wt % of beeswax and 27 wt % of polyethylene wax.

[0037] The mass percentage of each substance in the fiber component is 36wt% of chopped carbon fiber, 34wt% of chopped nylon fiber, and 30wt% of chopped aramid fiber; the diameters of the chopped carbon fiber, the chopped nylon fiber, and the chopped aramid fiber are all controlled within the range of 5-15μm, and the aspect ratio is all controlled within the range of 15-25:1.

[0038] The mass percentage of each substance in the whisker component is 25wt% polyamide whiskers, 40wt% chitin whiskers, and 35wt% cellulose whiskers; the diameters of the polyamide whiskers, the chitin whiskers, and the cellulose whiskers are all controlled within the range of 0.5-1μm, and the aspect ratios are all controlled within the range of 5-15:1.

[0039] The mass percentage of each substance in the biomass component is 41wt% of soybean oil, 31wt% of chlorella powder, and 28wt% of spirulina powder; the chlorella powder and the spirulina powder both include three particle sizes, namely, a particle size of 18-30μm, a particle size of 5-18μm, and a particle size of 0-5μm, and the mass ratio of the particle size of 18-30μm, the particle size of 5-18μm, and the particle size of 0-5μm are all 1:1.8:2.8.

[0040] This embodiment further provides a method for pre-waxing a complex structure multi-layer wall ceramic core, using the aforementioned low-temperature pre-waxing material for the complex structure multi-layer wall ceramic core. The pre-waxing method includes the following steps in order: Step 1: Prepare low-temperature pre-filled wax material according to the designed process flow and process parameters; Step 2: Load the prepared low-temperature pre-filled wax material into the wax injection gun, and control the temperature of the low-temperature pre-filled wax material in the wax injection gun to maintain appropriate fluidity to ensure smooth subsequent wax injection operations; Step 3: According to the designed process parameters, use a wax injection gun to inject wax into the small areas of the complex structure multi-wall ceramic core. After wax injection, let it stand for a certain period of time. After the escaped wax flow is initially solidified, use a tool to clean up the escaped excess wax flow. This completes the pre-wax filling process of the complex structure multi-wall ceramic core, and at the same time, a pre-wax filled complex structure multi-wall ceramic core is obtained.

[0041] In step 1, the method for preparing the low-temperature pre-filled wax material comprises the following steps in order: Step 1.1: Weigh all raw materials according to the designed material ratio; Step 1.2: Place all of the chopped carbon fibers, chopped nylon fibers, and chopped aramid fibers in the fiber component and the polyamide whiskers, chitin whiskers, and cellulose whiskers in the whisker component into a V-type mixer and mix them at room temperature for 25 minutes at a mixing speed of 150 r / min to uniformly disperse the materials to obtain a fiber-whisker multi-size reinforcement material, which is then removed for later use. Step 1.3: Place all the chlorella powder and spirulina powder of various particle sizes into a V-type mixer and mix them at room temperature for 15 minutes at a mixing speed of 150 r / min to uniformly mix the materials to obtain composite algae powder, which is then removed for later use. Step 1.4: Place all the surfactant substances, including stearic acid, fatty acid, and sodium dodecylbenzenesulfonate, into a blender and heat while stirring at a speed of 350 r / min. After heating to 100°C, continue stirring for 35 minutes to allow the substances to blend together to obtain the surfactant. Remove the mixture and keep it warm for later use. Step 1.5: Place all the paraffin components (46# semi-refined paraffin, 48# fully refined paraffin, 52# fully refined paraffin, 58# fully refined paraffin, and 60# fully refined paraffin) into a blender and heat while stirring at a speed of 250 r / min. After the temperature reaches 88°C, continue stirring for 25 minutes to completely melt the components. Step 1.6: Maintaining the stirring temperature and speed unchanged, add 85 wt% of the surfactant into the blender and continue stirring for 1.5 h to allow the substances to blend. Step 1.7: Maintaining the stirring temperature and speed unchanged, add the bonding wax to the blender and continue stirring for 25 minutes to allow the substances to blend. Step 1.8: Keeping the stirring temperature and speed constant, add all the beeswax and polyethylene wax in the modifier into the blender and continue stirring for 1.5 hours to allow the substances to blend together. Step 1.9: Maintaining the stirring temperature and speed, add 15 wt% of the surfactant and the soybean oil from the biomass component to the blender and continue stirring for 1.5 h to allow the substances to blend. Step 1.10: Maintaining the stirring temperature and speed, add the fiber-whisker multi-size reinforcement material and the composite algae powder into the blender and continue stirring for 4 hours to ensure that all materials are evenly mixed. Step 1.11: Maintaining the stirring temperature and stirring speed unchanged, add the graphene to the blender and continue stirring for 6.5 hours to ensure that all substances are evenly mixed, thereby obtaining the low-temperature pre-filled wax material; Step 1.12: The prepared low-temperature pre-filled wax material is injection molded, cooled and demolded to obtain an ingot, which is sealed and stored for subsequent pre-filled wax process of complex structure multi-layer wall ceramic core.

[0042] In step 2, the temperature of the low-temperature pre-filled wax material in the wax injection gun is controlled to be 68°C.

[0043] In step three, the small-sized areas in the complex structure multi-layer wall ceramic core include double-layer gaps, channel gaps, transverse ribs, cover plates and impact holes; the wax injection pressure is 0.4MPa, the wax injection speed is 10ml / s, and the straight-line distance between the wax injection gun tip and the filling position is 10mm.

[0044] When injecting wax into double-layer gaps and channel gaps, move the wax injection gun uniformly along the length of the gap at a speed of 20 mm / s. When injecting wax into transverse ribs and cover plates, select several injection points and inject 1.2 ml of wax per injection. Repeat the injection process several times. When injecting wax into impact holes, align the wax injection gun tip with the center of the impact hole and inject wax perpendicular to the hole end face until the wax protrudes from the hole end face. After injection, let the wax stand for 2 minutes, then use a tool to clean up any excess wax.

[0045] For chlorella and spirulina powder, you can directly purchase algae powder with three particle sizes that meet the requirements of this example. Ensure the algae powder is dry, free of moisture, or has a very low moisture content (no more than 1%). More preferably, purchase algae powder with a particle size range of 50-80 μm and pre-treat the coarse-particle algae powder to obtain algae powder with three particle sizes that meet the requirements of this example. Pre-treat the coarse-particle algae powder using the following method.

[0046] First, the coarse-grained chlorella powder and spirulina powder were placed in a drying oven for drying at a temperature of 110°C for 1.5 hours. After drying, they were taken out and naturally cooled to room temperature.

[0047] Then, the dried chlorella powder and spirulina powder were placed in a muffle furnace for gradient calcination treatment, namely: the temperature was raised from room temperature to 250°C at a heating rate of 8°C / min, kept warm for 25 minutes, and the residual trace moisture was slowly removed, and volatile small molecular organic matter was removed at the same time; the temperature was continued to be raised to 400°C at a heating rate of 4°C / min, kept warm for 55 minutes, and organic matter, such as protein and polysaccharides, was slowly removed; the temperature was continued to be raised to 570°C at a heating rate of 8°C / min, kept warm for 25 minutes, and then cooled to room temperature with the furnace to completely remove the residual organic matter.

[0048] Finally, the calcined chlorella powder and spirulina powder are ground and sieved respectively to meet the particle size grade of the present invention.

[0049] In this embodiment, the low-temperature pre-filled wax material prepared is as follows Figure 1 As shown, the low temperature pre-filled wax material is injection molded to obtain an ingot as shown in FIG. Figure 2 As shown, the pre-filling wax operation for the double-layer gap is as follows Figure 3 As shown, the pre-filling wax operation for the channel gap is as follows Figure 4 The whole ceramic core is pre-filled with wax. The local state of the ceramic core surface that has not been cleared after wax injection is as shown in the figure. Figure 5 As shown in the figure, the local state of the ceramic core surface after wax injection and wax removal is as follows: Figure 6 The wax mold that was pre-filled with wax and then pressed was subjected to X-ray inspection. The inspection results are shown in the figure below. Figure 7 As shown in the figure, it can be seen that the core is intact and there is no breakage.

[0050] The low-temperature pre-filled wax material and pre-filled wax method for the complex structure multi-layer wall ceramic core of this embodiment have the following beneficial effects: (1) The pre-filled wax material has a small solidification shrinkage, so that the wax material pre-filled into the multi-layer wall core will not generate excessive stress on the core during the solidification process, thereby avoiding core fracture. (2) The pre-filled wax material has moderate fluidity and can be injected using a wax injection gun. There will be no wax dripping due to the wax liquid being too thin, nor will there be wax blockage due to the wax liquid being too thick, thereby ensuring a smooth filling process. (3) The pre-filled wax material has a high strength. While preventing the wax mold from shrinking too much, it can also effectively reinforce the ceramic core and significantly improve the ceramic core's resistance to fracture during the circulation or wax pressing process. (4) After the wax mold is pressed and the shell is made, the pre-filled wax material can be completely removed as the shell is dewaxed and fired, resulting in a low residual ash content and a reduced blade inclusion defect rate.

[0051] Example 2: According to another preferred embodiment of the present invention, the low-temperature pre-wax material and pre-wax method for complex structure multi-layer ceramic cores are substantially the same as those in the first embodiment, except that: The mass percentage of each substance in the low-temperature pre-filling wax material is 46wt% paraffin component, 9wt% surfactant, 6wt% modifier, 6wt% fiber component, 5.5wt% whisker component, 5wt% graphene, 0.5wt% biomass component, and 22wt% bonding wax.

[0052] The mass percentage of each substance in the paraffin component is 11wt% of 46# semi-refined paraffin, 21wt% of 48# fully refined paraffin, 20wt% of 52# fully refined paraffin, 25wt% of 58# fully refined paraffin, and 23wt% of 60# fully refined paraffin.

[0053] The mass percentages of the surfactants are 40 wt % of stearic acid, 36 wt % of fatty acid, and 24 wt % of sodium dodecylbenzenesulfonate. The mass percentages of the modifiers are 66 wt % of beeswax and 34 wt % of polyethylene wax.

[0054] The mass percentages of the fiber component are 30wt% of chopped carbon fibers, 37wt% of chopped nylon fibers, and 33wt% of chopped aramid fibers. The mass percentages of the whisker component are 27wt% of polyamide whiskers, 35wt% of chitin whiskers, and 38wt% of cellulose whiskers.

[0055] The mass percentage of each substance in the biomass component is 35wt% of soybean oil, 33wt% of chlorella powder, and 32wt% of spirulina powder; the chlorella powder and the spirulina powder both include three particle sizes, and the mass ratios of the particle size of 18-30μm, the particle size of 5-18μm, and the particle size of 0-5μm are all 1:1.5:2.5.

[0056] In step 1, the preparation method of the low-temperature pre-filled wax material includes the following main parameters: step 1.2: putting the various substances in the fiber component and the various substances in the whisker component into a V-type mixer, mixing them at room temperature for 20 minutes, and a mixing speed of 200r / min to obtain a fiber-whisker multi-size reinforced material; step 1.3: putting chlorella powder and spirulina powder into a V-type mixer, mixing them at room temperature for 10 minutes, and a mixing speed of 200r / min to obtain a composite algae powder; step 1.4: putting the various substances in the surfactant into a blender, stirring and heating at a stirring speed of 300r / min, and continuing to stir for 30 minutes after the temperature is heated to 90°C to obtain Surfactant; Step 1.5: Place each substance in the paraffin component into a blender, heat while stirring, and continue stirring for 20 minutes after the temperature is heated to 80°C; Step 1.6-Step 1.11: Keep the stirring temperature and stirring speed unchanged, add 80wt% of the surfactant and continue stirring for 1 hour, add the bonding wax and continue stirring for 20 minutes, add each substance in the modifier and continue stirring for 1 hour, add 20wt% of the surfactant and soybean oil and continue stirring for 1 hour, add the fiber-whisker multi-size reinforcement material and the composite algae powder and continue stirring for 3 hours, add the graphene and continue stirring for 5 hours to obtain a low-temperature prefilled wax material.

[0057] In step 2, the temperature of the low-temperature pre-filled wax material in the wax injection gun is controlled to be 60°C.

[0058] In step three, the wax injection pressure is 0.2 MPa, the injection rate is 15 ml / s, and the linear distance between the wax injection gun tip and the filling position is 5 mm. When injecting wax into double-layer gaps and channel gaps, the wax injection gun movement speed is 10 mm / s. When injecting wax into transverse ribs and cover plates, the injection volume per injection point is 0.5 ml / time. After injection, let the wax stand for 1 minute and clean up the excess wax.

[0059] For chlorella powder and spirulina powder, algae powder with a particle size of 50-80 μm was purchased for pretreatment. The pretreatment process included the following main parameters: (1) drying temperature was 100 °C and drying time was 2 h. (2) the temperature was raised from room temperature to 200 °C at a rate of 5 °C / min and kept at this temperature for 30 min to slowly remove residual trace moisture and small molecular organic matter; the temperature was further raised to 300 °C at a rate of 3 °C / min and kept at this temperature for 60 min to slowly remove organic matter; the temperature was further raised to 500 °C at a rate of 5 °C / min and kept at this temperature for 30 min to completely remove residual organic matter.

[0060] Example 3: According to another preferred embodiment of the present invention, the low-temperature pre-wax material and pre-wax method for complex structure multi-layer ceramic cores are substantially the same as those in the first embodiment, except that: The mass percentage of each substance in the low-temperature pre-filling wax material is 53wt% of paraffin component, 6wt% of surfactant, 9wt% of modifier, 10wt% of fiber component, 8wt% of whisker component, 1wt% of graphene, 1wt% of biomass component, and 12wt% of bonding wax.

[0061] The mass percentage of each substance in the paraffin component is 15wt% of 46# semi-refined paraffin, 15wt% of 48# fully refined paraffin, 25wt% of 52# fully refined paraffin, 19wt% of 58# fully refined paraffin, and 26wt% of 60# fully refined paraffin.

[0062] The mass percentages of the surfactants are 53 wt % of stearic acid, 29 wt % of fatty acids, and 18 wt % of sodium dodecylbenzenesulfonate. The mass percentages of the modifiers are 80 wt % of beeswax and 20 wt % of polyethylene wax.

[0063] The mass percentages of the fiber component are 43wt% of chopped carbon fibers, 30wt% of chopped nylon fibers, and 27wt% of chopped aramid fibers. The mass percentages of the whisker component are 26wt% of polyamide whiskers, 38wt% of chitin whiskers, and 36wt% of cellulose whiskers.

[0064] The mass percentage of each substance in the biomass component is 50wt% of soybean oil, 25wt% of chlorella powder, and 25wt% of spirulina powder; the chlorella powder and the spirulina powder both include three particle sizes, and the mass ratios of the particle size of 18-30μm, the particle size of 5-18μm, and the particle size of 0-5μm are all 1:2:3.

[0065] In step 1, the preparation method of the low-temperature pre-filled wax material includes the following main parameters: step 1.2: putting the various substances in the fiber component and the various substances in the whisker component into a V-type mixer, mixing them at room temperature for 30 minutes, and a mixing speed of 100r / min to obtain a fiber-whisker multi-size reinforced material; step 1.3: putting chlorella powder and spirulina powder into a V-type mixer, mixing them at room temperature for 20 minutes, and a mixing speed of 100r / min to obtain a composite algae powder; step 1.4: putting the various substances in the surfactant into a blender, stirring and heating at a stirring speed of 400r / min, and continuing to stir for 40 minutes after the temperature is heated to 110°C to obtain to surfactant; Step 1.5: Place each substance in the paraffin component into a blender, heat while stirring, and continue stirring for 30 minutes after the temperature is heated to 95°C; Step 1.6-Step 1.11: Keeping the stirring temperature and stirring speed unchanged, add 90wt% of the surfactant and continue stirring for 2 hours, add the bonding wax and continue stirring for 30 minutes, add each substance in the modifier and continue stirring for 2 hours, add 10wt% of the surfactant and soybean oil and continue stirring for 2 hours, add the fiber-whisker multi-size reinforcement material and the composite algae powder and continue stirring for 5 hours, add the graphene and continue stirring for 8 hours to obtain a low-temperature prefilled wax material.

[0066] In step 2, the temperature of the low-temperature pre-filled wax material in the wax injection gun is controlled to be 75°C.

[0067] In step three, the wax injection pressure is 0.5 MPa, the injection rate is 5 ml / s, and the linear distance between the wax gun tip and the filling position is 15 mm. When injecting wax into double-layer gaps and channel gaps, the wax gun movement speed is 30 mm / s. When injecting wax into transverse ribs and cover plates, the injection volume per injection point is 2 ml / time. After injection, let the wax stand for 3 minutes and clean up the excess wax.

[0068] For chlorella powder and spirulina powder, algae powder with a particle size of 50-80 μm was purchased for pretreatment. The pretreatment process included the following main parameters: (1) drying temperature was 120℃ and drying time was 1 hour. (2) the temperature was raised from room temperature to 290℃ at a rate of 10℃ / min and kept at this temperature for 20 minutes to slowly remove the residual trace moisture and small molecular organic matter; the temperature was further raised to 490℃ at a rate of 5℃ / min and kept at this temperature for 50 minutes to slowly remove the organic matter; the temperature was further raised to 640℃ at a rate of 10℃ / min and kept at this temperature for 20 minutes to completely remove the residual organic matter.

[0069] Comparative Example 1: Pure paraffin wax, containing 100% by weight of 58# fully refined paraffin wax, is used as the pre-fill wax material. Pre-fill wax method: Place the paraffin wax in a container and heat it to 85-95°C to melt it. Place the melted paraffin wax into a wax injection gun, maintaining the temperature at 70-80°C. Use the wax injection gun to inject wax into the fine details of the double-walled ceramic core at a pressure of 0.3-0.4 MPa and a rate of 8-12 ml / s. After injection, wait 2-3 minutes and clean up any excess wax with a tool.

[0070] Comparative Example 2: Pure beeswax, containing 100% by weight, is used as the pre-fill wax material. To pre-fill the wax: Place the beeswax in a container and heat it to 70-80°C to melt it. Place the melted beeswax into a wax injection gun and maintain the temperature at 60-70°C. Use the wax injection gun to inject wax into the fine details of the double-walled ceramic core at a pressure of 0.3-0.4 MPa and a rate of 5-8 ml / s. After injection, wait 1-2 minutes and clean any excess wax with a tool.

[0071] The pre-filled wax materials prepared in the above three embodiments and two comparative examples were respectively used to fill the multi-layer wall ceramic core, and the pre-filled wax materials and the pre-filled wax process were tested. The test results are shown in Table 1.

[0072] Table 1 Test results of different pre-waxing materials and pre-waxing processes It can be seen from the above test results that the pre-filled wax materials prepared in the three embodiments have small solidification shrinkage, moderate fluidity and high strength, which can effectively reinforce the ceramic core and prevent it from breaking during the circulation and wax pressing process. The wax mold and shell can be completely removed after pressing, without ash residue, avoiding blade inclusion, and solving many problems existing in the prior art.

[0073] The raw materials used in the above examples, such as the paraffin component, surfactant, modifier, fiber component, whisker component, graphene, bonding wax, and biomass component, were purchased from Aladdin Reagent Co., Ltd. and Sinopharm Chemical Reagent Co., Ltd.

[0074] Special Note: The technical solution of this invention involves numerous parameters, and the synergistic effects between these parameters must be comprehensively considered to achieve the beneficial effects and significant improvements of this invention. Furthermore, the value ranges of each parameter in the technical solution were obtained through extensive testing. The inventors have recorded extensive experimental data for each parameter and their combinations. Due to space limitations, the specific experimental data will not be disclosed here.

[0075] Those skilled in the art will readily understand that the present invention encompasses any combination of the components described in the Summary and Detailed Description of the Invention and the accompanying drawings. Due to space limitations and for the sake of clarity, not all of the various solutions resulting from these combinations are described. Any modifications, equivalent substitutions, and improvements within the spirit and principles of the present invention are intended to be within the scope of protection of the present invention.

Claims

1. A low-temperature pre-filled wax material for a complex structure multi-layer wall ceramic core, characterized in that: The mass percentages of the various substances in the low-temperature pre-filling wax material are as follows: paraffin component 46-56wt%, surfactant 6-9wt%, modifier 6-9wt%, fiber component 6-10wt%, whisker component 5-8wt%, graphene 1-5wt%, biomass component 0.5-1wt%, and bonding wax 12-22wt%, and the sum of the contents of the various substances is 100wt%.

2. The low-temperature pre-filled wax material for a complex structure multi-layer wall ceramic core according to claim 1, characterized in that: The mass percentage of each substance in the paraffin component is 10-15wt% of 46# semi-refined paraffin, 15-21wt% of 48# fully refined paraffin, 19-25wt% of 52# fully refined paraffin, 19-25wt% of 58# fully refined paraffin, and 22-27wt% of 60# fully refined paraffin.

3. The low-temperature pre-filled wax material for a complex structure multi-layered ceramic core according to claim 2, characterized in that: The mass percentage of each substance in the surfactant is 40-53wt% of stearic acid, 25-39wt% of fatty acid, and 13-27wt% of sodium dodecylbenzenesulfonate.

4. The low-temperature pre-filled wax material for a complex structure multi-layer wall ceramic core according to claim 3, characterized in that: The mass percentage of each substance in the modifier is 66-80wt% of beeswax and 20-34wt% of polyethylene wax.

5. The low-temperature pre-filled wax material for a complex structure multi-layer wall ceramic core according to claim 4, characterized in that: The mass percentage of each substance in the fiber component is 30-43wt% of chopped carbon fiber, 28-40wt% of chopped nylon fiber, and 25-37wt% of chopped aramid fiber; the diameters of the chopped carbon fiber, the chopped nylon fiber, and the chopped aramid fiber are all controlled within the range of 5-15μm, and the aspect ratio is all controlled within the range of 15-25:

1.

6. The low-temperature pre-filled wax material for a complex structure multi-layer wall ceramic core according to claim 5, characterized in that: The mass percentage of each substance in the whisker component is 25-30wt% polyamide whiskers, 35-40wt% chitin whiskers, and 35-40wt% cellulose whiskers; the diameters of the polyamide whiskers, the chitin whiskers, and the cellulose whiskers are all controlled within the range of 0.5-1μm, and the aspect ratios are all controlled within the range of 5-15:

1.

7. The low-temperature pre-filled wax material for a complex structure multi-layered ceramic core according to claim 6, characterized in that: The mass percentage of each substance in the biomass component is 35-50wt% of soybean oil, 25-38wt% of chlorella powder, and 22-35wt% of spirulina powder; the chlorella powder and the spirulina powder both include three particle sizes, namely, a particle size of 18-30μm, a particle size of 5-18μm, and a particle size of 0-5μm, and the mass ratios of the particle size of 18-30μm, the particle size of 5-18μm, and the particle size of 0-5μm are all 1:1.5-2:2.5-3.

8. A wax pre-filling method for a ceramic core with a complex structure and multiple walls, characterized in that: The low-temperature pre-filling wax material for a complex structure multi-layer wall ceramic core according to any one of claims 1 to 7 is used, and the pre-filling wax method comprises the following steps in order: Step 1: Prepare low-temperature pre-filled wax material according to the designed process flow and process parameters; Step 2: Load the prepared low-temperature pre-filled wax material into the wax injection gun, and control the temperature of the low-temperature pre-filled wax material in the wax injection gun to maintain appropriate fluidity to ensure smooth subsequent wax injection operations; Step 3: According to the designed process parameters, use a wax injection gun to inject wax into the small areas of the complex structure multi-wall ceramic core. After wax injection, let it stand for a certain period of time. After the escaped wax flow is initially solidified, use a tool to clean up the escaped excess wax flow. This completes the pre-wax filling process of the complex structure multi-wall ceramic core, and at the same time, a pre-wax filled complex structure multi-wall ceramic core is obtained.

9. The wax pre-filling method for a complex structure multi-layer wall ceramic core according to claim 8, characterized in that: In step 1, the method for preparing the low-temperature pre-filled wax material comprises the following steps in order: Step 1.1: Weigh all raw materials according to the designed material ratio; Step 1.2: Place all of the chopped carbon fibers, chopped nylon fibers, and chopped aramid fibers in the fiber component and the polyamide whiskers, chitin whiskers, and cellulose whiskers in the whisker component into a V-type mixer, mix them at room temperature for 20-30 minutes at a mixing speed of 100-200 r / min to uniformly disperse the materials, and obtain a fiber-whisker multi-size reinforcement material, which is then removed for later use. Step 1.3: Place all the chlorella powder and spirulina powder of various particle sizes into a V-type mixer and mix them at room temperature for 10-20 minutes at a mixing speed of 100-200 r / min to uniformly mix the materials to obtain composite algae powder, which is then removed for later use. Step 1.4: Place all the surfactant substances, including stearic acid, fatty acid, and sodium dodecylbenzenesulfonate, into a blender and heat while stirring at a speed of 300-400 r / min. After the temperature reaches 90-110°C, continue stirring for 30-40 minutes to allow the substances to blend together to obtain the surfactant. Remove the mixture and keep it warm for later use. Step 1.5: Place all the paraffin components, including 46# semi-refined paraffin, 48# fully refined paraffin, 52# fully refined paraffin, 58# fully refined paraffin, and 60# fully refined paraffin, into a blender and heat while stirring at a speed of 200-300 r / min. After the temperature reaches 80-95°C, continue stirring for 20-30 minutes to completely melt the components. Step 1.6: Maintaining the stirring temperature and stirring speed unchanged, add 80-90 wt% of the surfactant into the blender and continue stirring for 1-2 hours to allow the substances to blend together; Step 1.7: Keeping the stirring temperature and speed constant, add the bonding wax into the blender and continue stirring for 20-30 minutes to allow the substances to blend together. Step 1.8: Keeping the stirring temperature and speed constant, add all the beeswax and polyethylene wax in the modifier into the blender and continue stirring for 1-2 hours to allow the substances to blend together. Step 1.9: Maintaining the stirring temperature and speed, add 10-20 wt% of the surfactant and the soybean oil from the biomass component to the blender and continue stirring for 1-2 hours to allow the substances to blend. Step 1.10: Maintaining the stirring temperature and speed, add the fiber-whisker multi-size reinforcement material and the composite algae powder into the blender and continue stirring for 3-5 hours to ensure that all materials are evenly mixed. Step 1.11: Maintaining the stirring temperature and stirring speed unchanged, add the graphene to the blender and continue stirring for 5-8 hours to ensure that all substances are evenly mixed, thereby obtaining the low-temperature pre-filled wax material; Step 1.12: The prepared low-temperature pre-filled wax material is injection molded, cooled and demolded to obtain an ingot, which is sealed and stored for subsequent pre-filled wax process of complex structure multi-layer wall ceramic core.

10. The wax pre-filling method for a complex structure multi-layer wall ceramic core according to claim 8, characterized in that: In step 2, the temperature of the low-temperature pre-filled wax material in the wax injection gun is controlled to be 60-75°C; In step 3, the small areas in the complex multi-wall ceramic core include double-layer gaps, channel gaps, transverse ribs, cover plates, and impact holes; the wax injection pressure is 0.2-0.5 MPa, the wax injection speed is 5-15 ml / s, and the linear distance between the wax injection gun tip and the filling position is 5-15 mm; When injecting wax into double-layer gaps and channel gaps, move the wax injection gun at a uniform speed along the length of the gap, with a moving speed of 10-30mm / s; when injecting wax into transverse ribs and cover plates, select several wax injection points, and the injection amount of wax at each wax injection point is 0.5-2ml / time, and each wax injection point is repeated several times; when injecting wax into impact holes, align the gun head of the wax injection gun with the center of the impact hole, and inject wax perpendicular to the end face of the hole until the wax material protrudes from the end face of the hole; after letting it stand for 1-3 minutes after wax injection, use a tool to clean up the excess wax flow that has escaped.

Citation Information

Patent Citations

  • Packing mold material used in investment precision casting

    CN102876054A

  • Precise casting wax and preparation method thereof

    CN110684314A

  • Preparation method of mullite whisker reinforced aluminum-based ceramic core for directional solidification

    CN112047726A

  • Filling type investment casting pattern material with high filler content and preparation method of filling type investment casting pattern material

    CN112920611A

  • Ceramic core with multi-layer wall structure and preparation method of ceramic core

    CN116020977A